Pengaruh Anti-Fraud Awareness dan Big Five Personality Traits terhadap Kecenderungan Accounting Fraud: Studi pada Pengelola Bumdes Se-Kabupaten Buleleng - Diantari, Ketut Risma; Prayudi, Made Aristia; Savitri, Ni Luh Asri (Vokasi : Jurnal Riset Akuntansi, 2025)
The purpose of this research is to find out the influence of anti-fraud awareness and big five personality traits on the tendency of accounting fraud in BUMDes managers in Buleleng Regency. In the sampling process, purposive sampling techniques are used where BUMDes that meet the criteria are 34 BUMDes involving 100 respondents. This research uses a quantitative approach with instruments in the form of questionnaires measured using a five-point Likert scale and the data is then processed using SPSS version 22 software and the tests carried out include descriptive statistical tests, data quality tests, classical assumptions tests, and hypothesis tests. The results of this study show: (1) Anti-fraud awareness has a significant negative effect on the tendency of accounting fraud. (2) Openness to experience has a significant negative effect on the tendency of accounting fraud. (3) Consientiousness does not have a significant effect on the tendency of accounting fraud. (4) Extraversion has a significant positive effect on the tendency of accounting fraud. (5) Agreeableness has a significant negative effect on the tendency of accounting fraud. (6) Neuroticism has a significant negative effect on the tendency of accounting fraud. Keywords : anti-fraud awareness, big five personality traits, tendency of accounting fraud